2017
DOI: 10.1111/acps.12724
|View full text |Cite
|
Sign up to set email alerts
|

Insula and amygdala resting‐state functional connectivity differentiate bipolar from unipolar depression

Abstract: Objective Distinguishing depressive episodes due to bipolar disorder (BD) or major depressive disorder (MDD) solely on clinical grounds is challenging. We aimed at comparing resting-state functional connectivity (rsFC) of regions subserving emotional regulation in similarly depressed BD and MDD. Method We enrolled 76 inpatients (BD, n=36; MDD, n=40), and healthy controls (HC, n=40). A seed-based approach was used to identify regions showing different rsFC with the insula and the amygdala. Insular and amygdal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 63 publications
6
45
0
1
Order By: Relevance
“…Additionally, we found that both disorders shared common FDG uptake alterations in insula compared to HC, which is in line with previous evidence reporting insula as a key region associated with BD and mood disorders in general . This structure seems to be responsible for the detection of emotional salience and the integration of sensory, emotional and cognitive information and it is a critical node within the salience network, along with amygdala and anterior cingulate cortex .…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we found that both disorders shared common FDG uptake alterations in insula compared to HC, which is in line with previous evidence reporting insula as a key region associated with BD and mood disorders in general . This structure seems to be responsible for the detection of emotional salience and the integration of sensory, emotional and cognitive information and it is a critical node within the salience network, along with amygdala and anterior cingulate cortex .…”
Section: Discussionsupporting
confidence: 91%
“…These findings indicate that the aforementioned nodes are more integrated into the brain network of BD patients than in networks of individuals not suffering from BD, possibly leading to a disturbed perception of emotions in BD. Changes in the limbic system supporting our results were both found in resting‐state paradigms (Ambrosi et al, ; Anand et al, ; Lois, Linke, & Wessa, ; Wang, Wang, Jia, Zhong, Zhong et al, ) as well as in task‐based paradigms (Gruber et al, ; Strakowski, Adler, Holland, Mills, & DelBello, ; Thermenos et al, ; Townsend & Altshuler, ). In most studies, irregularities were registered in the frontal lobes along with temporal and subcortical regions such as hippocampus and basal ganglia.…”
Section: Discussionsupporting
confidence: 87%
“…These findings indicate that the aforementioned nodes are more integrated into the brain network of BD patients than in networks of individuals not suffering from BD, possibly leading to a disturbed perception of emotions in BD. Changes in the limbic system supporting our results were both found in resting-state paradigms(Ambrosi et al, 2017;Anand et al, 2009;Lois, Linke, & Wessa, 2014; as well as in task-based paradigms…”
supporting
confidence: 90%
“…Psychiatric inpatients ( N = 423) were recruited from the Menninger Clinic in Houston, Texas as a part of the McNair Initiative for Neuroscience Discovery—Menninger/Baylor (MIND‐MB) research study . Inpatients were eligible if mentally stable enough to participate, had no contraindications for magnetic resonance imaging (MRI), and gave signed, informed consent (procedures were approved by the Institutional Review Board).…”
Section: Methodsmentioning
confidence: 99%